التربية والتعليم والشؤون الثقافية في ظل نظام رضا شاه بهلوي ( 1925 – 1941 ) - ال طويريش, ا.د. موسى محمد; خلف, محمد حاتم (مجلة دراسات في التاريخ والآثار, 2020)
AbstrictReached the conclusion to a group of the most prominent Alasantajat1-Reza Shah Pahlavi, the pace of modernizing steps in the field of Education and Cultural Affairs simulation of the West, and put up its own system mimics the West and apply it in the scientific life.-2 did not take these steps in the field of Education and Cultural Affairs of the final Mdyatea because of religious opposition, which has faced, because pulling out of religious education ESTABLISHMENT it would lose money and privileges are endless.3-clerics turned into bitter enemies of the regime of Reza Shah Pahlavi, because of the procedures in the field of Education and Cu